2013
DOI: 10.1371/journal.pone.0056711
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of CpG Islands among HBV Genotypes

Abstract: DNA methylation is being increasingly recognized to play a role in regulation of hepatitis B virus (HBV) gene expression. The aim of this study was to compare the CpG island distribution among different HBV genotypes. We analyzed 176 full-length HBV genomic sequences obtained from the GenBank database, belonging to genotypes A through J, to identify the CpG islands in the HBV genomes. Our results showed that while 79 out of 176 sequences contained three conventional CpG islands (I–III) as previously described,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 46 publications
(54 reference statements)
5
63
0
1
Order By: Relevance
“…The HBV cccDNA genome contains three predicted CpG islands: (1) the region overlapping the start site of the S gene (Island 1); (2) the region encompassing enhancer I, the HBx gene promoter (Xp), and the core promoter (Cp) (Island 2); and (3) the region harboring the Sp1 promoter and the start codon of the pol gene (Island 3; Fig. ) . Among the 10 distinct genotypes (A‐J) of HBV, the methylation rates in Island 1 are variable, whereas Islands 2 and 3 are more conserved across genotypes .…”
Section: Epigenetic Control Of Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBV cccDNA genome contains three predicted CpG islands: (1) the region overlapping the start site of the S gene (Island 1); (2) the region encompassing enhancer I, the HBx gene promoter (Xp), and the core promoter (Cp) (Island 2); and (3) the region harboring the Sp1 promoter and the start codon of the pol gene (Island 3; Fig. ) . Among the 10 distinct genotypes (A‐J) of HBV, the methylation rates in Island 1 are variable, whereas Islands 2 and 3 are more conserved across genotypes .…”
Section: Epigenetic Control Of Hbv Infectionmentioning
confidence: 99%
“…(25,26) Among the 10 distinct genotypes (A-J) of HBV, the methylation rates in Island 1 are variable, whereas Islands 2 and 3 are more conserved across genotypes. (26) Methylation of the CpG islands on HBV cccDNA regulates HBV replication and gene expression. Zhang et al demonstrated that cccDNA CpG Island 1 is seldom methylated, methylation of CpG Island 2 is associated with low viremia, and methylation of CpG Island 3 may contribute to a lower serum HBsAg level in CHB patients.…”
Section: Hbv-dna Methylationmentioning
confidence: 99%
“…HBV cccDNA contains three major CpG islands that can potentially be methylated (Zhang et al, 2013). Accumulating evidence suggests that variable degrees of CpG methylation were present in cccDNA from patients with chronic HBV infection.…”
Section: Structure and Function Of Cccdna Minichromosomementioning
confidence: 99%
“…The HBV genome has 2–3 conventional CpG islands depending on the geno type [166,167]. Interestingly, these CpG islands are found at strate gic locations in the regulatory elements of the HBV genome [168].…”
Section: Hbv-based Viral Dna Markersmentioning
confidence: 99%